Performance of Strelitzia reginae Flowers Dye as Sensitizer for New Dye-Sensitized Solar Cell Fabrication - Al-Alwani, Mahmoud A. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In current study, the dye from flowers petals of Strelitzia reginae used for the first time to prepare natural photosensitizer for DSSC fabrication. Among five different solvents used to extract the natural dye from S. reginae flowers, the ethanol extract of anthocyanin dye revealed higher absorption spectrum of 0.757a.u. at wavelength of 454nm.  A major effect of temperature was studied to increase the extraction yield. The results show that the optimal temperature was 70 Â°C and there was a sharp decrease of dye concentration from 0.827 at temperature of 70 Â°C to 0.521 at temperature of 90Â°C. The extract solution of flowers of S. reginae showed higher concentration in acidic media, especially at pH 4 (0.902). The C, H, N elemental analyses of natural extract showed the presence of N (10.52%), C (18.97%) and H (2.229%) contents.  The presence of anthocyanin in the extract of S. reginae and their functional groups were determined using UV-Vis spectroscopy and Fourier-Transform Infrared Spectroscopy (FTIR). The optical properties of deposited TiO2 thin film were studied using scanning electron microscope (SEM) and X-Ray Diffraction (XRD). In Addition, other confirmation that dye supported surface of TiO2, inhibition of crystallinity of TiO2 was investigated by the Energy Disperse X-ray (EDX) analysis. According to experimental results, the conversion efficiency of DSSC fabricated using anthocyanin dye obtained from S. reginae flowers was 0.1%, with short-circuit current (Isc) of 0.6 mA/cm-2, open-circuit voltage (Voc) of 0.51 V and fill factor (FF) of 36.83%.